World agriculture - Ottenheimer, Laurence (Mankato, Minn. : Creative Education, 1988)
Presents an historical perspective in a description of how all kinds of plant and animal foods from around the world are grown, harvested, and consumed.
Cover title.
Includes index.
Keywords: Agriculture -- Juvenile literature; Food -- Juvenile literature; Agriculture; Food